Anti Measure Noise Research of Morphing Wing UAV. (2015) - Haoqin, Su; Xiaoxiang, Bao; Hongwei, Shi; Kai, Liu; Jing, Song
Abstract: The morphing UAV (Unmanned Aerial Vehicle) is a tendency for the future of UAV. When UAV changes construct of wings, measure noise disturbance probably meet, then UAV bears larger change of aerodynamic force and moment, it's for morphing UAV to find a robust to fit this condition. This paper brings out LQG controller, which can solve measure noise problems and control 6 freedom affine nonlinear equations. Simulation of morphing process is realized with LQG controller, which validate the stability and robust of LQG robust controller.